Giberela em trigo: controle químico e tecnologia de aplicação de fungicidas - Bonfada, Éverson Bilibio (2018)
The wheat is one of the most important cereals for human and animal feed. Among the factors that can affect the crop yield and the grain´s quality, it stands out the fusarium head blight (Triticum aestivum), a disease considered of difficult control, in a scenario in which there are obstacles in the application technology, by the difficulty of deposition of drops in sites of infection and low efficacy of fungicides. The general goals were: check if different groups of chemical fungicides, used separately or in combination are effective in the control of the fusarium head blight of wheat, and assess whether changes in application technology can improve the efficiency of chemical control of the fusarium head blight in two wheat cultivars. In addition, this work is divided into two chapters. In chapter I, three experiments were performed in the harvest of 2016, and three in the harvest of 2017. The treatments consisted of applying separately or in combination or a commercial mixture of chemical groups triazol, estrobilurina, benzimidazol, ditiocarbamato, quinona, carboxamida, triazolintiona and pirazol carboxamida. The delineation of the treatments was the unifactorial model, with a number of distinct treatments in each experiment, and the trial design in blocks randomly with four replications, cultivate TBIO Toruk (moderately susceptible – MS the fusarium head blight)4. It was evaluated the intensity of the fusarium head blight, effectiveness of control, accumulation of deoxynivalenol (DON) in grains, weight of hectolitre, a thousand grains of weight and income. The data were subjected to analysis of variance (F-Test) and the comparison of averages by the Scott-Knott test, both at 5%. In chapter II, two experiments were performed in the first harvest and one experiment on the second. The treatments consisted of two configurations of the sprayer boom (with and without assistance of curtain of chains) and different types of nozzles/spray tips. In both harvest, the delineation of treatments was in the bifactorial model (with/without using the spacebar versus models/nozzle tips) and the experimental in randomized blocks with three replications (2016 harvest) and four (2017 harvest), cultivars TBIO Toruk and Sossego (MS the fusarium head blight). In this chapter, it was also evaluated the spray deposition on hydrosensitive roles. The data were subjected to analysis of variance (F-Test) and the comparison of average by Tukey test, both at 5%. It was concluded that the chemical group separately benzimidazol gives the reduction of the intensity of fusarium head blight. The association of the fungicide dithiocarbamates to benzimidazole and/or the commercial mixture of Triazol + strobilurins contributes to the improvement of the control of the disease. The pyraclostrobin interferes in the intensity of the fusarium head blight in the cobs and has variable effects on the accumulation of DON in grains. The sequential application of commercial mixture of etrobilurin + triazolinethione, in higher doses, shows an increase in the effectiveness of control and grain yield. The use of aid to the bar provides increments in grain yield which are variable according to the environmental conditions in each wheat harvest. This same factor, presents a variation on the intensity of the disease. The cultivars respond differently to treatments applied; the interaction models of tip/tip versus aid to the sprayer boom, have an influence on the accumulation of DON in grains.